Salt-kneading: alternative sizing of active pharmaceutical ingredients - Šimek, Michal; Vyňuchal, Jan; Tomášová, Lea (Pharmaceutical development and technology, 2016)
The most of currently produced active pharmaceutical ingredients (APIs) are poorly soluble in the human body. One of the options how to increase their dissolution rate is reducing their particle size. If very small particles of API are desired, traditional milling methods often cause smeared, agglomerated or non-flowing particles due to the forces applied. We tried to compare some of milling methods with the salt-kneading method, which is not typically used in the pharmaceutical industry. Salt-kneading process is driven by several variable parameters (e.g. the amount, hardness and particle size of the salt-kneading material), which influence the degree of size reduction of API particles which are chafed by a surplus of salt-kneading material. A model poorly-soluble API was separately processed with oscillation mill, vibratory mill and kneader; and the morphology, size distribution and solid form of prepared particles were analyzed. Our basic variation of salt-kneading parameters showed the potential of the salt-kneading method, which appears a very effective method of API controlled reduction. The final size can be modified according to the amount and properties of the salt-kneading material. The availability of such a method equips pharmaceutical scientists with a size-reduction method that provides very small, rounded and free-flowing particles of the poorly soluble API and reduces non-preferred needle shape.
Keywords: farmaceutická technologie; pomocné látky; Technology, Pharmaceutical; léčivé přípravky; rozpustnost; Excipients; Sodium Chloride; chlorid sodný; Particle Size; Pharmaceutical Preparations; velikost částic; Solubility